IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA IPS TERPADU DI SMP PANCA SETYA 2 SINTANG - Darsela, Darsela; Pelipa, Emilia Dewiwati; Thoharudin, Munawar (STKIP Persada Khatulistiwa Sintang, 2024)
The education system in Indonesia has undergone several curriculum changes over time, one of which is the implementation of the â€œMerdeka Belajarâ€ curriculum as an evaluation of its predecessor, the 2013 curriculum. This curriculum was designed to adapt to the educational needs during the COVID-19 pandemic. This research aims to elucidate how the â€œMerdeka Belajarâ€ curriculum is implemented in the integrated social studies subject for eighth-grade students at SMP Panca Setya 2 Sintang. The research methodology employed is qualitative descriptive with data collection techniques including observation, interviews, and documentation. Primary data were obtained from interviews with the school principal, vice principal of the curriculum, social studies teachers, and eighth-grade students, while secondary data included reading materials and documents. Data analysis followed the interactive model proposed by Miles and Huberman, encompassing data collection, reduction, display, and verification. The research findings indicate that the implementation of the â€œMerdeka Belajarâ€ curriculum is progressing well, although teachers require assistance in its execution. Challenges encountered include difficulties in fostering creative learning processes, limited references, unequal access to learning, and time management issues. Recommendations to address these challenges include utilizing the â€œMerdeka Mengajarâ€ platform and enhancing digital access for all stakeholders involved in the learning process.